2022
DOI: 10.3390/v14051105
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutically Active Minibody Exhibits an Antiviral Activity in Oseltamivir-Resistant Influenza-Infected Mice via Direct Hydrolysis of Viral RNAs

Abstract: Emerging Oseltamivir-resistant influenza strains pose a critical public health threat due to antigenic shifts and drifts. We report an innovative strategy for controlling influenza A infections by use of a novel minibody of the 3D8 single chain variable fragment (scFv) showing intrinsic viral RNA hydrolyzing activity, cell penetration activity, and epidermal cell penetration ability. In this study, we examined 3D8 scFv’s antiviral activity in vitro on three different H1N1 influenza strains, one Oseltamivir-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…depending on the IAV strain, NVLH8 demonstrated the specific neutralization activity (H1N1/pdm, H3N2/Brisbane, H3N2/ Switzerland), which supported that they are specific to H1N1/PR8 (Supplementary Figure S3B). In a previous study, a 3D8 scFv was able to hydrolyze RNA in RNP form, resulting in an antiviral activity against influenza viruses (Lee et al, 2022). Here, we strongly agree that the 3D8 scFv digested RNA in RNP form, particularly to H1N1/PR8 strain.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…depending on the IAV strain, NVLH8 demonstrated the specific neutralization activity (H1N1/pdm, H3N2/Brisbane, H3N2/ Switzerland), which supported that they are specific to H1N1/PR8 (Supplementary Figure S3B). In a previous study, a 3D8 scFv was able to hydrolyze RNA in RNP form, resulting in an antiviral activity against influenza viruses (Lee et al, 2022). Here, we strongly agree that the 3D8 scFv digested RNA in RNP form, particularly to H1N1/PR8 strain.…”
Section: Discussionsupporting
confidence: 88%
“…Our previous study reported the antiviral activity of 3D8 scFv against influenza H1N1/H275Y virus through hydrolyzing viral RNA in mRNA and vRNPs and cRNPs form (Lee et al, 2022). Here, we strongly agreed that 3D8 scFv targeted not only mRNA (naked RNA) but also vRNA and cRNA in RNP forms (vRNPs or cRNPs) of H1N1/PR8.…”
Section: Influenza Antiviral Synergistic Effects In a Combination Wit...supporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, vaccine production time is a bottleneck, so vaccines are not readily available during the initial spread of a pandemic. As such, alternative treatments such as novel mini-antibodies have been proposed [ 1 ]. Human influenza A vaccines constitute the cornerstone of flu prevention while drugs have been developed for monotherapeutic purposes in the early stages of infection or as a co-medication, such as orally inhaled zanamivir (Relenza™) or orally administered oseltamivir (Tamiflu™).…”
Section: Introductionmentioning
confidence: 99%